Self‐healing hydrogel of poly(vinyl alcohol)/graphite oxide with pH‐sensitive and enhanced thermal properties. Issue 17 (8th January 2018) - Wang, Sui; Zhang, Zheng; Chen, Bing; Shao, Jia; Guo, Zhiyong
ABSTRACT: Supramolecular hydrogel is a fascinating polymeric material composed of three‐dimensional noncovalent networks with many outstanding properties, especially reversible relevant performances. A self‐healing supramolecular hydrogel of poly(vinyl alcohol)/graphite oxide, with reversible pH responsiveness and good thermal stability, was prepared. The morphology, functional group changes, swelling performance, thermal stability, rheological performance, and self‐healing property of the PVA/GO hydrogel were investigated. A probable mechanism between the components and potential applications were also examined in our study. The experimental results show that the PVA/GO hydrogel was not only self‐healable without external stimulus or addition of any healing agents, but also pH sensitive and with good thermal stability. Green ingredients (PVA and GO) and a simple synthesis method (a freezing/thawing treatment) may pose little threat to the environment and also promote the production of such hydrogels. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46143. Abstract :